Highly compressible ceramic/polymer aerogel-based piezoelectric nanogenerators with enhanced mechanical energy harvesting property - Ram, Farsa; Suresh, Karthika; Torris, Arun; Kumaraswamy, Guruswamy; Shanmuganathan, Kadhiravan (Ceramics International, 2021)
Ceramic piezoelectric materials have orders of magnitude higher piezoelectric coefficients compared to polymers. However, their brittleness precludes imposition of large strains in mechanical energy harvesting applications. We report here that ice templating affords low bulk modulus lead-free aerogel piezoelectric nanogenerators (PENG) with unprecedented combination of flexibility and high piezoelectric response (voltage and power density). A modified ice templating protocol was used to fabricate piezoelectric nanocomposites of surface modified BaTiO3 (BTO) nanoparticles in crosslinked polyethylene imine. This protocol allowed incorporating a significantly high fraction of BTO particles (up to 83 wt %) in the aerogel, while retaining remarkably high compressibility and elastic recovery up to 80% strain. The output voltage, at an applied compressive force of 20 N (100 kPa), increased with BTO loading and a maximum output voltage of 11.6 V and power density of 7.22 ?W/cm2 (49.79 ?W/cm3) was obtained for PENG aerogels containing 83 wt% BTO, which is orders of magnitude higher than previously reported values for foam-based piezoelectric energy harvesters. The BTO/PEI PENGs also showed cyclic stability over 900 cycles of deformation. PENGs with higher porosity showed better elastic recovery and piezoelectric properties than lower porosity and higher BTO content aerogels. To the best of our knowledge, this is the first report to demonstrate the piezoelectric properties of high ceramic content aerogels having very high compressibility and elastic recovery.
Keywords: Ceramic polymer aerogels; energy harvesting; ice templating; piezoelectric